2012
DOI: 10.1016/j.seizure.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcome following minimal access subtemporal selective amygdalohippocampectomy

Abstract: The present study provides a detailed account of neurocognitive outcome following minimal access subtemporal selective amygdalohippocampectomy (SAH) and establishes rates of neurocognitive decline in the largest sample to date. Use of a subtemporal surgical approach to SAH has been proposed to possibly reduce the risk for postoperative neurocognitive decline since lateral neocortical tissues is not resected and the temporal stem is preserved. The current study extends prior research with subtemporal SAH patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 63 publications
4
12
0
Order By: Relevance
“…In recent studies it was found that approximately one-third of patients who underwent SAH on the left side of the brain had loss of memory, verbal intellect, and naming, whereas patients who had surgery on the right side of the brain mainly had loss of visual memory. 2,3 Our results seem to confirm the findings of previous studies in which loss of verbal memory was reported after surgery on the dominant side of the brain; however, we cannot determine whether it is due to any disruption of unknown functional networks of mesial temporal lobe structures. Further studies are warranted to clarify these results.…”
Section: Discussionsupporting
confidence: 87%
“…In recent studies it was found that approximately one-third of patients who underwent SAH on the left side of the brain had loss of memory, verbal intellect, and naming, whereas patients who had surgery on the right side of the brain mainly had loss of visual memory. 2,3 Our results seem to confirm the findings of previous studies in which loss of verbal memory was reported after surgery on the dominant side of the brain; however, we cannot determine whether it is due to any disruption of unknown functional networks of mesial temporal lobe structures. Further studies are warranted to clarify these results.…”
Section: Discussionsupporting
confidence: 87%
“…Thus subtemporal patients displayed a considerably (up to sixfold) increased risk of decline in visual/figural learning compared with transsylvian operated patients. Similar negative effects of subtemporal SAH on figural memory after left and right surgery have been obtained in a recent prospective but uncontrolled study on cognitive outcome of a large sample of 53 patients using the BVMT-R (Brief Visual Spatial Memory Test-Revised) with reliability of change indices for determination of individual change 43. While systematic changes in memory after temporal lobe surgery have mainly be described for verbal memory after left temporal resection, this is the first time that in two independent studies a negative effect of temporal lobe surgery on visual/figural memory is evident.…”
Section: Discussionsupporting
confidence: 73%
“…Dominant hemispheric resection is often associated with cognitive declines in naming and verbal learning, while non-dominant hemispheric resection is associated with impaired nonverbal memory, object recognition and figural learning 37. SAH may provide better neurocognitive outcomes than ATL 38.…”
Section: Discussionmentioning
confidence: 99%